Prominent Judicial Measures Applicable to Combat the Rising Complexity of Juvenile Delinquency in Developing Countries (Lex Scientia Law Review, 2025)
Adopting international legal instruments and judicial models is critical for developing countries to better handle the increasing complexity of juvenile delinquency. These instruments and models formulate frameworks to balance the need for public safety with the rights and rehabilitation of juvenile offenders. This qualitative study aimed to exploit the secondary resources by employing a structural approach of comparative law methods and the most-similar and most-different systems design to propose the best strategy for addressing the rising complexity of juvenile delinquency in developing countries, taking Vietnam as a representative example. The results indicate that a hybrid approach prioritizing the Restorative and Welfare models for long-term rehabilitation, supported by Retributive measures in cases where deterrence is necessary, is likely the most practical solution in developing countries. While Restorative justice offers community-led resolutions and the Welfare model tackles root causes of delinquency, these require long-term investment and systemic support. In contrast, Retributive justice provides immediate responses but fails to resolve the deeper issues that drive juvenile delinquency. The research implications can help policymakers and justice systems in developing countries make informed decisions, considering the cultural, economic, and social context to effectively formulate a juvenile justice system that combats and prevents troublesome juvenile delinquency.